Moringa oleifera and Azadirachta indica Leaves Enriched Diets Mitigate Chronic Oxyfluorfen Toxicity Induced Immunosuppression through Disruption of Pro/Anti-Inflammatory Gene Pathways, Alteration of Antioxidant Gene Expression, and Histopathological Alteration in Oreochromis niloticus - Rowida E. Ibrahim; Heba I. Ghamry; Saed Ayidh Althobaiti; Daklallah A. Almalki; Medhat S. Shakweer; Mona A. Hassan; Tarek Khamis; Heba M. Abdel-Ghany; Shaimaa A. A. Ahmed (Fishes, 2022)
Our goal in this study was to determine the effect of dietary supplementation with Moringa oleifera (M. oleifera), and Azadirachta indica (A. indica) leaves in mitigating the effects of chronic oxyfluorfen (OXY) toxicity on the health status, expressions of immune and antioxidant genes, and tissue morphological alterations in Oreochromis niloticus. In this study, we used 370 healthy O. niloticus (average weight = 25.35 ± 0.29 g). We used 70 fish to study the 96 h lethal concentration 50 (LC50) of OXY. We assigned another 300 fish into six equal groups with five replicates (50 fish/group, 10 fish/replicate) to determine the chronic OXY toxicity for 60 days. The 96 h LC50 of OXY for O. niloticus was 6.685 mg/L. Exposure to 1/10 96 h LC50 of OXY (0.668 mg/L) had health impacts and pathological changes in the main tissues. In addition, the expressions of oxidant and immune genes were disrupted. Dietary supplementation with both M. oleifera and A. indica efficiently mitigated the toxic effects of OXY in the treated groups. Comparing the palliative efficiency of M. oleifera and A. indica, the results showed that M. oleifera was more potent in alleviating the toxic effects of OXY.